Analysis of Shots Trajectory and Effectiveness in Women’s and Men’s Football European Championship Matches - Blanca De-la-Cruz-Torres; Miguel Navarro-Castro; Anselmo Ruiz-de-Alarcón-Quintero (Big Data and Cognitive Computing)
Shots on target are a crucial factor in football performance, yet the impact of categorizing shots as low or ground-level and high or parabolic has not been fully explored. The objective of this study was to analyze whether there are differences in the frequency and effectiveness (as measured by xGOT) between parabolic and low shots on target in international men’s and women’s football competitions. The results revealed that the most common shot type was the parabolic shot, occurring in 59.86% of shots on goal in the men’s competition (270 shots) and 67.12% in the women’s competition (196 shots). In the overall set of shots, 62.77% were parabolic (466 shots). No significant differences were observed between the competitions (p > 0.05). Regarding the xGOT values, no significant differences were observed for any of the interaction effects analyzed (gender, shot type and shot outcome). The conclusion was that the parabolic shot was the most frequent type of shot on target in both men’s and women’s football.